Online Media Usage in Guidance and Counseling Services during Covid-19 Pandemic - Hastuti, Maria Margaretha Sri; Tyas, Prias Hayu Purbaning (Jurnal Kajian Bimbingan dan Konseling, 2021)
The Covid-19 pandemic has brought restraints into people’s activities. Consequently, during the pandemic, the school guidance and counseling services should be conducted online. Therefore, this study seeks to identify the types of online media frequently used by school counselors in classical guidance and individual or group counseling, as well as the rationale. This descriptive quantitative study involved 106 school counselors and used an Online Media Usage questionnaire to obtain the data. The results suggest that Google Form and Google Classroom have become the most used applications in classical guidance, while WhatsApp is the most popular application for individual or group counseling. These applications are selected due to the limited internet access, students’ technological literacy, students’ financial state, and privacy assurance, primarily for the counseling process. Therefore, the school counselors mainly provide asynchronous rather than synchronous services during the Covid-19 pandemic. Besides, these results can be the foundation for online guidance and counseling services development.